A computational approach to optimal control problems subject to mixed control-state constraints - Zhu, Jinghao (International journal of control, 2023)
In this paper, we study a computational approach to Hamilton-Jacobi-Bellman (HJB) equation for singular optimal control subject to mixed control-state constraints. A nonlinear diffusion equation is presented for the viscosity approximation to a partial differential equation by rewriting HJB equation. We construct a so called extremal flow for approximating the optimal objective value of the singular optimal control problem by a differential-algebraic equation. Some examples are given to illustrate this computational approach.